PENGARUH RETURN ON ASSET, DEBT TO EQUITY RATIO DAN CURRENT RATIO TERHADAP HARGA SAHAM PT. ULTRAJAYA MILK INDUSTRY & TRADING COMPANY TBK PERIODE TAHUN 2010-2023 - Nurafita Indah Sari; Amthy Suraya (Journal of Research and Publication Innovation, 2025)
This study aims to determine the effect of Return on Assets, Debt to Equity Ratio, and Current Ratio on the Share Price of PT Ultrajaya Milk Industry & Trading Company Tbk for the period 2010-2023, partially or simultaneously. The analytical methods used in this research are descriptive statistical analysis, classical assumption test, simple linear regression analysis, multiple linear regression analysis, coefficient of determination (Adjusted R2), t test and f test using the SPSS version 29 application. The results of this study show that partially the variable Return on Assets (ROA) has a tcount of 1,654 (<2,2284) with a probability value of 0,129 (>0,05) so that the variable Return on Assets (ROA) partially has no effect on Stock Prices. The Debt to Equity Ratio (DER) variable has a tcount of 1,390 (<2.22814) with a probability value of 0,195 (>0,05) so that the Debt to Equity Ratio (DER) variable partially has no effect on Stock Prices. The Current Ratio (CR) variable has a tcount of 1,914 (<2,22814) with a probability of 0,085 (>0,05) so that the Current Ratio (CR) variable partially has no effect on Stock Prices. Simultaneously, the variables Return on Assets (ROA), Debt to Equity Ratio (DER), and Current Ratio (CR) have an Fcount of 5,135 (>3,71) with a probability value of 0,021 (<0,05) which means simultaneous Return on Assets (ROA), Debt to Equity Ratio (DER), and Current Ratio (CR) have a significant effect on stock prices.